PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA KELAS V TEMA 4 SEHAT ITU PENTING UPTDSD NEGERI 091608 SINAKSAK - Anggita Theresia Pandiangan; Rio Parsaoran Napitupulu; Desi Sijabat (JOURNAL SAINS STUDENT RESEARCH, 2024)
Thils relselarch ailms to deltelrmilnel whelthelr thelrel ils an ilnfluelncel of thel Makel A Match Lelarnilng Modell on thel Scilelncel Lelarnilng Outcomels of Class V Studelnts at UPTD SD Nelgelril 091608 Silnaksak. Thils typel of relselarch ils quantiltatilvel relselarch wilth elxpelrilmelntal relselarch melthods. Thel data collelctilon telchnilquels useld iln thils relselarch arel obselrvatilon and telsts. Thel telst telchnilquel that willl bel gilveln iln thils relselarch ils usilng multilplel choilcel quelstilons as a prel-telst and post-telst whilch havel a valuel of (1) ilf thel answelr ils correlct and a valuel of (0) ilf thel answelr ils wrong, thel telst willl bel gilveln belforel and aftelr thel trelatmelnt. Data analysils telchnilquels welrel carrileld out usilng normalilty telsts and hypothelsils telsts. Thel relsults of thel t telst show that t ils (15.860). Melanwhillel, thel ttablel wilth lelvells ils 24 so thel ttablel ils (1,711) wilth a silgnilfilcant lelvell (-2 tailleld). So wel gelt (15.860 > 1.711). So ilt can bel concludeld that thelrel ils an ilnfluelncel of thel makel a match lelarnilng modell on studelnt lelarnilng outcomels iln thelmel 4 that helalth ils ilmportant iln class V UPTD SD Nelgelril 091608 Silnaksak, so Ha ils accelpteld and H0 ils reljelcteld.